The Impact and Cost of Power Load Shedding to Domestic Consumers (The Pakistan Development Review, 2013)
The widespread and growing phenomenon of power load shedding has emerged as one of the principal supply-side constraints to growth of the economy of Pakistan. Not only has this led to significant losses of output, employment and exports but also during periods of high outages there have been large-scale protests, particularly in Punjab and KPK. Households have faced severe disruptions due to the high and growing incidence of load shedding. These have led to mass protests on streets resulting in disruption of other economic activities. As such, the economic return of reducing outages and of facilitating the process of adjustment to these outages is likely to be high. This paper provides an approach and methodology for quantifying cost of load shedding to households in Pakistan. It is organised as follows: Section 2 highlights some key trends in the power sector of Pakistan. Section 3 will present a detailed literature review on the methodology used for quantification of costs due to outages. Section 4 describes the methodology used for qualification of costs due to outages and for estimation of willingness to pay. Section 5 presents estimates of the cost of load shedding in the domestic sector of Pakistan. Finally, Section 6 highlights the major policy implications emerging from the research.